Dialogues and essays / Seneca ; translated by John Davie ; with an introduction and notes by Tobias Reinhardt. - Seneca, Lucius Annaeus, ca. 4 B.C.-65 A.D.
Includes bibliographical references (p. [xxix]-xxxi)